Determinants of metastatic competency in colorectal cancer. Issue 1 (3rd January 2017) - Tauriello, Daniele V. F.; Calon, Alexandre; Lonardo, Enza; Batlle, Eduard
Abstract : Colorectal cancer (CRC) is one of the most common cancer types and represents a major therapeutic challenge. Although initial events in colorectal carcinogenesis are relatively well characterized and treatment for early‐stage disease has significantly improved over the last decades, the mechanisms underlying metastasis – the main cause of death – remain poorly understood. Correspondingly, no effective therapy is currently available for advanced or metastatic disease. There is increasing evidence that colorectal cancer is hierarchically organized and sustained by cancer stem cells, in concert with various stromal cell types. Here, we review the interplay between cancer stem cells and their microenvironment in promoting metastasis and discuss recent insights relating to both patient prognosis and novel targeted treatment strategies. A better understanding of these topics may aid the prevention or reduction of metastatic burden. Abstract : Colorectal cancer metastasis remains a major therapeutic challenge. In this review, Tauriello et al . discuss the interplay between cancer stem cells and their microenvironment during the metastatic process. Recent insights reveal opportunities for refined patient prognosis and suggest novel strategies for therapeutic intervention. Proposed treatments include targeting the crosstalk between cancer stem cells and the stroma, or the cells themselves.